PENGARUH SELF EFFICACY TERHADAP HASIL BELAJAR FISIKA MELALUI PENGGUNAAN MODEL PROBLEM BASED LEARNING - Biola Yoannita; Esmar Budi; Cecep E. Rustana (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Research has done experiment to know the influence of self efficacy of the results of the study physics material fluid static.This research used a quantitative approach with the experiment method, using pre experimental design kind of one group pretest-posttest design.The population of the research is all of students in senior high school 2 Indramayu.The sample done to technique nonprobability sampling by design purposive sampling.Data in this study obtained from the questionnaire and tests.Analysis techniques data using descriptive statistics, and statistika inferential.And testing hypotesis use the gains.From test it is known that the study results for the students with self efficacy low also low ( Ngain = 0,18 or 18 % ), the study results for the students with self efficacy being is low ( Ngain = 0,19 or 19 % ), and improving study results for the students with self efficacy high is being ( Ngain = 0,62 or 62 % ). Keywords: Study Results of Physics, Self Efficacy, Problem Based Learning.